Motivation as an Intervening Variable (Mediation) on Leadership Styles and Training in Performance Improvement - Novi Satria Jatmiko; Hermy Yunisa; Fauziah (Nusantara Innovation Journal, 2024)
This study aims to determine the influence of Motivation as an intervening variable (mediation) on Leadership Style and Training in Performance Improvement. The population and the sample in this study were 38 participants in the Leadership Administrator Force X training of the East Kalimantan Provincial Government. The study was conducted quantitatively using questionnaires and processed using Smart PLS version 4. The direct influence results obtained were that X1 (Leadership Style) had a positive effect with a value of 0.408 but was not significant with a statistical T value of 1.944 or a P value of 0.052 on X3 (Motivation); X1 (Leadership Style) has a positive effect with a value of 0.088 but is not significant with a statistical T value of 0.412 or a P value of 0.680 on Y (Performance); X2 (Training) has a positive effect with a value of 0.483 and is significant with a statistical T value of 2.723 or a P value of 0.006 on X3 (Motivation); X2 (Training) has a negative effect with a value of -0.355 and is significant with a statistical T value of 2.601 or a P value of 0.037 on Y (Performance); X3 (Motivation) has a positive effect with a value of 0.990 and is significant with a statistical T value of 4.924 or a P value of 0.000 on Y (Performance). The indirect influence produced by X3 (Motivation) can mediate and increase the value of Y (Performance), where X1 (Leadership Style) on Y (Performance) through P value 0.044.X3 (Motivation) can be a mediation that increases the value of Y (Performance) and changes it from negative (opposite) to positive, where it has a value of 2.244 or a P value of 0.025. With the results of this research, it is important to pay attention to motivating and mediating leadership styles and training to improve employee performance.